Impact of chronic kidney disease severity on causes of death after first-ever stroke: A population-based study using nationwide data linkage - Wu, Hsin-Hsu (PLoS One, 2020)
BACKGROUND: Stroke is prevalent in patients with chronic kidney disease (CKD) and is associated with high mortality, but the causes of death after stroke among different CKD stages are not well known. AIMS: We aimed to investigate whether the severity of CKD would impact on the causes of death after first-ever stroke. METHODS: This retrospective multicenter cohort study included stoke patients with CKD between 2007 and 2012. The cause of death and date of death were ascertained by linking the National Death Registry Database of Taiwan. Clinical outcomes, 1-month, and 1-year mortality rates, and major causes of death were compared according to five CKD stages (G1 to G5) in the ischemic and hemorrhagic stroke separately. RESULTS: Of these patients, 9,878 were first-ever ischemic stroke (IS) patients, and 1,387 were first-ever hemorrhagic stroke (HS) patients. Patients with CKD G5 had the highest one-year mortality rate with hazard ratio 5.28 [95%CI, 3.94–7.08] in IS and 3.03 [95%CI, 2.03–4.54] in HS when compared to G1 patients. Leading causes of one-year death after IS were stroke, cancer, and pneumonia in early (G1-3) CKD patients, while diabetes mellitus, CKD, and stroke itself contributed to the major mortality in CKD G5 patients. An inverse association between eGFR decrement and the proportion of deaths caused by stroke itself was observed in CKD G2-5 patients after IS. Stroke was the leading cause of one-year death among all CKD patients after HS. CONCLUSIONS: Asides from high mortality, late-stage CKD patients had different causes of death from early CKD patients after stroke. This study highlights the need to imply different treatment strategies in late-stage CKD post-stroke patients to improve their prognosis.